Extraction and Physicochemical Characterization of Pectin from Noni (Morinda citrifolia) Fruit - Maulani, Tuti Rostianti; Lioe, Hanifah Nuryani; Arief, Irma Isnafia; Kusumaningrum, Harsi Dewantari (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
Noni (Morinda citrifolia) is a popular plant in Asian countries and has great potential as pectin source for thickening agents in food products. In general, ethanol has been widely used to precipitate pectin, but the proportion can affect the quality of the product. Therefore, this study aimed to characterize the physicochemical properties of pectin from noni fruit. Extraction was performed using 0.1 N HCl at pH 1.5 and heated at 80°C for 15 min, followed by precipitation with different proportions of 96% ethanol including A (1:1), B (1:2), and C (1:3) v/v, while commercial orange pectin was used as a reference. The results showed that all pectin extracted belonged to the high methoxyl category. The FTIR spectra confirmed the presence of important functional groups including OH-hydroxyl, CH3-saturated aliphatic methyl, C=O carbonyl, and -O- cyclic ether. Furthermore, the crystalline and amorphous structures of noni pectin were confirmed by X-ray diffraction observation. The highest yield was achieved using the proportion of 1:3, followed by 1:2, and 1:1 on a wet basis. The MeO and AUA content of sample B (1:2) were relatively similar to those of the reference. Based on extraction results, noni possesses good characteristics and has the potential for commercial pectin production.